Variability of bronchial inflammation in chronic obstructive pulmonary disease: implications for study design. - Gamble, E; Qiu, Y; Wang, D; Zhu, J; Vignola, A; Kroegel, C; Morell, F; Hansel, T; Pavord, I; Rabe, K; Barnes, N; Jeffery, P (2006)
There is variability in the distribution of inflammatory cells in bronchial tissue in chronic obstructive pulmonary disease (COPD). Better strategies for biopsy sampling of the airway mucosa may improve the capacity to show a difference between study populations where variability in distribution exists. The current authors have examined sources of biological variability in the quantification of inflammatory cells in endobronchial biopsies using immunostained samples taken from 51 subjects with COPD, with a mean forced expiratory volume in one second of 1.71 L, 55% predicted. The distribution of variance contributed by different sources was similar for different inflammatory cell types. For CD8+ cells, a key inflammatory cell in COPD, the largest contribution to intra-subject variability (39%) was time (i.e. 10 weeks between biopsies of placebo-treated subjects), followed by airway generation (23%), biopsy (2.5%), zone (within section; 1.4%) and section (0.4%). Power calculations demonstrated that examining one section from one biopsy, from each of two airway generations, would require a sample size of 32 subjects per group to show a difference of one doubling or halving in CD8+ cells, compared with 47 subjects per group if only one airway generation was sampled. Therefore, biopsies from more than one airway generation should be examined in order to maximise statistical power to detect a difference between study groups.